Receiving Country Investments and Acquisitions: How Migrants Negotiate the Adaptation to Their Destination - Demireva, Neli (2019)
This article looks at the adaptation patterns of EU migrants—Bulgarian, Romanian, Italian and Spanish—in European markets, and uses several interviews of overseas non-EU migrants in the UK and Germany. The interaction of migrants with the receiving context is being considered. Drawing on several interviews with actual migrants and recruitment agents collected in the GEMM (Growth, Equal Opportunities, Migration and Markets) project in four major immigrant societies (Germany, UK, Spain and Italy), this article focuses on the receiving country acquisitions that facilitate the adaptation of migrants along their journeys. EU migrants have very different adaptation strategies to non-EU migrants, and this article comments on the differences observed as well as on the differences between them according to skill levels. Migrant adaptation challenges are acknowledged and studied dynamically. Thus, this unique data brings forward a multi-layered picture of the migrant adaptation process in Europe.